Analisa Perbandingan Quality of Service (QoS) Pada Jaringan Backbone Non-MPLS Dengan Jaringan Backbone MPLS Menggunakan Routing Protocol OSPF Di PT. Telekomunikasi Indonesia, Tbk. Witel Ridar Riau - Silaban, Nestor Hasudungan; Sari, Linna Oktaviana; Anhar, Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The development of telecommunications technology based on Internet Protocol (IP) is now growing with the competitiveness of the telecommunications company to improve the quality of service to consumers. It can be obtained by increasing the quality backbone network using Multi Protocol Label Switching (MPLS). MPLS is a new technology to forward the packet to the backbone network without changing the existing network structure. The main idea is to construct a replacement MPLS paths using label switching and distribute traffic into it. This paper compare the Qualty of Service (QoS) on Non-MPLS backbone network to MPLS backbone network with OSPF routing protocol on the PT. Telecommunication Indonesia, Tbk. Witel Ridar Riau. The Software simulation using Graphical Network Simulator (GNS3) is analyze by observing QoS are delay, packet loss, throughput, and jitter with Wireshark. In this research, there are two scenarios that will be analyzed. The first scenarios analyze the customer site make deliveries to one another customer site and the second scenarios analyze two customer sites make deliveries to the customer site simultaneously. The results show that the highest delay in the first scenario is better MPLS backbone network at 0.029999 s and 0.0124 s in the second scenario than Non-MPLS backbone network. It Followed by the highest value of packet loss on the network backbone MPLS and non-MPLS are equal 0% and in the second scenario, MPLS is better 0% than non-MPLS. The Throughput has same trend with the highest value in the first scenario MPLS backbone network is better 0.0085 Mbps and 0011 Mbps in the second scenario than Non-MPLS backbone network. Meanwhile the highest jitter values in the first scenario MPLS backbone network is better too at 0.3595995 s and 1.544403 s on the second scenario than the non-MPLS.Keywords : MPLS, OSPF,GNS3, QoS, Wireshark.